Pertanggungjawaban Pidana Koruptor di Rutan dan Upaya Peningkatan Kepercayaan Masyarakat - Serin Mustari; Ade Mahmud (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Corruption threatens the stability of democracy and public trust in legal institutions in Indonesia. The case of extortion in the KPK detention house involving internal employees has become a concern, where of the 93 employees allegedly involved, only 15 were made defendants even though the facts of the trial showed the involvement of other parties. This inconsistency is contrary to the principle of similia similibus. This study examines criminal liability and strategies to increase public trust in the KPK through normative juridical analysis. The results show that other parties who are proven to know and enjoy the results of extortion should also be held criminally liable. To restore public trust, the President's political will, institutional reform, recruitment improvements, strengthening ethical standards, resolving cases transparently, and the passage of the Asset Forfeiture Law are needed to strengthen the deterrent effect and eradicate corruption Abstrak. Korupsi mengancam stabilitas demokrasi dan kepercayaan publik terhadap institusi hukum di Indonesia. Kasus pemerasan di rumah tahanan KPK yang melibatkan pegawai internal menjadi perhatian, di mana dari 93 pegawai yang diduga terlibat, hanya 15 dijadikan terdakwa meski fakta persidangan menunjukkan keterlibatan pihak lain. Ketidakkonsistenan ini bertentangan dengan asas similia similibus. Penelitian ini mengkaji pertanggungjawaban pidana dan strategi peningkatan kepercayaan publik terhadap KPK melalui analisis yuridis normatif. Hasilnya menunjukkan bahwa pihak lain yang terbukti mengetahui dan menikmati hasil pemerasan seharusnya juga dimintai pertanggungjawaban pidana. Untuk memulihkan kepercayaan publik, diperlukan political will Presiden, reformasi kelembagaan, perbaikan rekrutmen, penguatan standar etik, penyelesaian kasus secara transparan, dan pengesahan Undang-Undang Perampasan Aset guna memperkuat efek jera dan pemberantasan korupsi.